Analysis of Promotion Effectiveness at PLN Traveling Booth for Optimizing Electricity Sales in Yogyakarta Region - istikhomah laila fadhilah; Albari (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the effectiveness of promotional strategies implemented through the Mobile Booth (SARLING) by PT PLN (Persero) UP3 Yogyakarta. SARLING serves as a traveling promotional booth that facilitates direct interaction with customers to enhance awareness and interest in PLN's electricity services. Despite its innovative approach, the effectiveness of this strategy remains questionable, particularly in terms of its impact on customer purchasing decisions and the rate of promotion cancellations. Addressing this gap, the research adopts a quantitative approach, utilizing electricity sales transaction data alongside surveys involving both customers and SARLING officers. The findings reveal that SARLING promotions significantly influence customer engagement and contribute to the increase in electricity sales transactions. However, several challenges persist, such as unclear promotional information and inadequate training for SARLING personnel. This study contributes to the body of knowledge on field-based promotional strategies in public utility services. Recommendations include improving the clarity of promotional materials, enhancing communication skills of SARLING officers, and optimizing the scheduling and location selection of the mobile booths to maximize outreach and impact.